Urbanization and its impact on Ghana’s rural transformation - Diao, Xinshen; Magalhaes, Eduardo; Silver, Jed (International Food Policy Research Institute, 2019)
The chapter addresses three broad questions. First, are patterns of rural employment in Ghana changing with urbanization and are those changes related in any systematic way with proximity to urban centers of different sizes? Second, does proximity to different-sized urban centers have any impact on patterns of agricultural intensification? Finally, what are the impacts on household livelihoods and welfare outcomes? To answer these questions the analysis goes beyond the usual agroecological breakdown (Chapter 4) and uses a spatial typology of rural areas based on work by Berdegue et al. (2015) and others in Latin America.